Physics based modeling and simulation of collision response - Abdul Rab, Abdul Rab (2004)
To make computer games more realistic, physics based modeling and simulation is becoming a popular area of game development. Objects, in games, need to move and interact realistically with one another. Quite often gamers ignore the classic Newtonian physics of real world, and play their own version of reality. It takes game away from reality. Physical parameters like gravity, velocity changes, inertia as well as the collision with the other objects and collision response must be considered while developing a computer game. The use of physics simulation is an important step that increases the overall level of realism; however this introduces a significant increase in complexity. The goal of this research work is to model and simulate the collision response between the regular shaped rigid or plastic objects with relative physics. In order to achieve this objective a mathematical model has been developed. Impulse based method has been implemented to approximate rigid body collision and their responses. In impulse-based method, an impulsive force is applied to each colliding object at the point or points of impact. This force can be calculated such that it changes the velocity of each object instantly, not allowing them to penetrate one another. Seven cases of collision with different parameters are discussed here and are compared with Chris Hecker’s work. It is found that the model developed is superior to Chris model because this model works for both headon and oblique collision while Chris model is only good for head-on collision. Results also show that this model is as good for the spheres of the same masses as it is for the spheres of different masses. Simultaneously it works for head on and oblique collisions. It is covenant with situations either the spheres are moving in the same direction or in the opposite direction. It has been modeled how much the spheres rebound away from each other after collision. Simulation of collision response also supports the mathematical calculations. The research work presented in this thesis shows a successful attempt of inclusion of physics in computer games.